2010
DOI: 10.1186/1758-2652-13-29
|View full text |Cite
|
Sign up to set email alerts
|

High rate of loss to clinical follow up among African HIV-infected patients attending a London clinic: a retrospective analysis of a clinical cohort

Abstract: BackgroundLong-term regular clinic follow up is an important component of HIV care. We determined the frequency and characteristics of HIV-infected patients lost to follow up from a London HIV clinic, and factors associated with loss to all HIV follow up in the UK.MethodsWe identified 1859 HIV-infected adults who had registered and attended a London clinic on one or more occasions between January 1997 and December 2005. Loss to follow up was defined as clinic non-attendance for one or more years. Through anony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
3
28
2
1
Order By: Relevance
“…Our findings are consistent with previous studies among UK populations in showing that disengagement from HIV care is more likely among women and less likely among MSM. 8,22 A study of gender disparities concluded that poorer engagement in HIV care by women was underpinned by a complex array of factors, 74 and findings from both our survey and analysis of UK CHIC data suggested that the association between gender and disengagement could be explained by other factors.…”
Section: Objective 2: Predictive Factors Of Disengagementmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings are consistent with previous studies among UK populations in showing that disengagement from HIV care is more likely among women and less likely among MSM. 8,22 A study of gender disparities concluded that poorer engagement in HIV care by women was underpinned by a complex array of factors, 74 and findings from both our survey and analysis of UK CHIC data suggested that the association between gender and disengagement could be explained by other factors.…”
Section: Objective 2: Predictive Factors Of Disengagementmentioning
confidence: 99%
“…Previous studies have examined the association between engagement in HIV care, as defined by one of the measures described above, and background characteristics. Although health service provision and populations of PLWH vary from country to country, these studies suggest that PLWH are less likely to disengage from care if they are male, 8 older, 8,21,28,29 white 8,22 and men who have sex with men (MSM) 22,23 and have started ART. 8,21 Socioeconomic factors and education have been highlighted in relation to disparities in EIC 30,31 and complex patient groups, such as intravenous drug users, migrants and the newly diagnosed, are more likely to disengage from care.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
See 3 more Smart Citations